Increased liver stiffness in alcoholic liver disease: differentiating fibrosis from steatohepatitis - Mueller, Sebastian; Millonig, Gunda; Sarovska, Lucie; Friedrich, Stefanie Sofia Anna; Reimann, Frank M.; Pritsch, Maria; Eisele, Silke; Stickel, Felix; Longerich, Thomas; Schirmacher, Peter; Seitz, Helmut K. (World journal of gastroenterology, 2010)
Increased liver stiffness in alcoholic liver disease: Differentiating fibrosis from steatohepatitis
Gesehen am 11.05.2023